Quaternized Chitosan-Based Anion Exchange Membrane Composited with Quaternized Poly(vinylbenzyl chloride)/Polysulfone Blend - Nhung, Le Thi Tuyet (Polymers (Basel), 2020)
An efficient and effective process for the production of high-performance anion exchange membranes (AEMs) is necessary for the commercial application of fuel cells. Therefore, in this study, quaternized poly vinylbenzyl chloride (QVBC) and polysulfone were composited with glycidyltrimethylammonium-chloride-quaternized chitosan (QCS) at different ratios (viz., 1 wt %, 5 wt %, and 10 wt %). The structure and morphology of the membranes were characterized by Fourier transform infrared spectroscopy and scanning electron microscopy, respectively. Further, the water uptake, swelling ratio, and ionic conductivities of the composite membrane at different wt % of QCS were evaluated. The membrane with 5% QCS exhibited an ionic conductivity of 49.6 mS/cm and 130 mS/cm at 25 °C and 70 °C, respectively.